2019
DOI: 10.1111/jbi.13734
|View full text |Cite
|
Sign up to set email alerts
|

Model complexity affects species distribution projections under climate change

Abstract: Aim: Statistical species distribution models (SDMs) are the most common tool to predict the impact of climate change on biodiversity. They can be tuned to fit relationships at various levels of complexity (defined here as parameterization complexity, number of predictors, and multicollinearity) that may co-determine whether projections to novel climatic conditions are useful or misleading. Here, we assessed how model complexity affects the performance of model extrapolations and influences projections of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 44 publications
1
125
1
Order By: Relevance
“…Firstly, we extracted all variables for the extent of the range of each taxon, resampled onto a 5km x 5km equal-area grid and projected them into the WGS 1984 geographic coordinate system. Secondly, we used Spearman rank correlations to select a subset of least correlated variables to minimize multicollinearity (Brun et al, 2019). For this, we used a graphical representation of the correlation values between variables to identify five least correlated variables for each species to avoid overfitting in model predictions ( Fig.…”
Section: Predictor Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we extracted all variables for the extent of the range of each taxon, resampled onto a 5km x 5km equal-area grid and projected them into the WGS 1984 geographic coordinate system. Secondly, we used Spearman rank correlations to select a subset of least correlated variables to minimize multicollinearity (Brun et al, 2019). For this, we used a graphical representation of the correlation values between variables to identify five least correlated variables for each species to avoid overfitting in model predictions ( Fig.…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Modelling species responses to global environmental changes carries many uncertainties (Araújo & New, 2007;Thuiller et al, 2019). Using two algorithm approaches, two future scenarios, two dispersal scenarios, an ensemble forecasting and including only a few but highly important predictors of the distribution of African apes, should have reduced uncertainties in our distribution models (Brun et al, 2019;Thorne et al, 2013). A recent study proposed that SDMs include historical records to produce better predictions of range shifts rather than relying on contemporary records alone (Faurby & Araújo, 2018).…”
Section: Limitations Of Distribution Modelsmentioning
confidence: 99%
“…The selection of pseudo-absence or background data is a third key consideration in SDM building, given that the majority of species observations concern presence-only data (Ponder et al, 2001). The impact of predictor set, modeling technique, and pseudo-absence selection on the performance of bioclimatic envelope models has been studied in isolation (Barbet-Massin et al, 2012;Beaumont et al, 2005;Moreno-Amat et al, 2015;Pearson et al, 2006;Pliscoff et al, 2014) or for two of the three factors (Brun et al, 2019;Bucklin et al, 2015;Dormann et al, 2008;Jarnevich et al, 2017;Petitpierre et al, 2017;Verbruggen et al, 2013;Warren et al, 2019). However, to our knowledge, no study so far has systematically evaluated the combined effect of predictor set, modeling technique, and pseudo-absence selection on the performance of bioclimatic envelope models.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that highly correlated environmental variables are not a problem when the aim of the study is prediction in the same extent of the observed data, reducing collinearity is recommended in order to reduce model complexity and increase the interpretability of the predictors (Dormann et al., 2013; Merow et al., 2013). In addition, although the degree of accepted model complexity varies according to the modeling scope(s) (Halvorsen, 2012; Halvorsen, Mazzoni, Bryn, & Bakkestuen, 2015), it has been pointed out that models might perform best when trained with a reduced number of predictors (Brun et al., 2020; Halvorsen et al., 2015). Even though the selection should be driven by the knowledge of the modeled species, this might be difficult when the user must decide among several a priori ecologically relevant predictors for the species, or if the ecology of the species is poorly known.…”
Section: Discussionmentioning
confidence: 99%